2009
DOI: 10.1364/oe.17.011986
|View full text |Cite
|
Sign up to set email alerts
|

Robust orthogonal parameterization of evolution strategy for adaptive laser pulse shaping

Abstract: Many spectroscopic applications of femtosecond laser pulses require properly-shaped spectral phase profiles. The optimal phase profile can be programmed on the pulse by adaptive pulse shaping. A promising optimization algorithm for such adaptive experiments is evolution strategy (ES). Here, we report a four fold increase in the rate of convergence and ten percent increase in the final yield of the optimization, compared to the direct parameterization approach, by using a new version of ES in combination with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…The patterns associated with similar-parity orders feature a reduced symmetry, compared to quasi-symmetric patterns of oppositeparity orders. These symmetries are very similar to the 2D polynomial landscapes of second harmonic generation [68,71].…”
Section: D Landscapessupporting
confidence: 52%
See 2 more Smart Citations
“…The patterns associated with similar-parity orders feature a reduced symmetry, compared to quasi-symmetric patterns of oppositeparity orders. These symmetries are very similar to the 2D polynomial landscapes of second harmonic generation [68,71].…”
Section: D Landscapessupporting
confidence: 52%
“…Replacing the spectral phase basis of a coherent control experiment with appropriate linear combinations of the basis functions can result in a new landscape with more convex contours, less shear, and even separable phase terms [68,71]. This technique can also be used successfully in the case of a CARS experiment.…”
Section: Modified Basis Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…At low levels of signal to noise ratio, the learning process does not start in the first place, as small improvements of the fitness function are comparable or negligible compared to noise level. We studied this effect previously and proposed to use orthogonal functions for robust implementations [18]. Here, we consider a different type of noise, which is more common in coherent control experiments, and study its effect on original and modified φ 2 -φ 4 landscapes of the SHG process.…”
Section: Noisementioning
confidence: 99%
“…Previously, Roslund et al reported a comprehensive study of the reduced landscape of the SHG process with three degrees of freedom [17] and also a statistical steepest-ascent technique to probe the local structure of the landscape [13]. We reported the changes of a solution landscape in the context of robust and orthogonal parameterization of an evolutionary algorithm [18]. In this work, we study the properties of 1D, 2D, and 3D landscapes of the SHG process by including up to the sixth order phase term.…”
Section: Introductionmentioning
confidence: 98%